Impacts of tree species admixing on soil carbon and soil properties in boreal conifer-dominated forests: Evidence from multiple datasets - Anna Repo; Päivi Soronen; Timo Domisch; Saija Huuskonen; Hannu Ilvesniemi; Aleksi Lehtonen; Jari Miina; Mari Myllymäki; Aino Smolander (Forest Ecology and Management, 2026)

Supported superbase shaped solid sorbents for CO2 capture - Baljeet Singh; Zahra Eshaghi Gorji; Risto Koivula; Timo Repo (Chemical Engineering Journal, 2025)

Sustainable urban mining of silver with fatty acids - Anže Zupanc; Joseph Install; Timo Weckman; Marko M. Melander; Marianna Kemell; Karoliina Honkala; Timo Repo (Chemical Engineering Journal, 2025)

Indoor direct air capture using amorphous MOF pellets from blast furnace slag: Waste to porous functional materials - Baljeet Singh; Marianna Kemell; Mikko J. Heikkilä; Timo Repo (Chemical Engineering Journal, 2025)

Functionalization of nitrogen-doped graphene quantum dot: A sustainable carbon-based catalyst for the production of cyclic carbonate from epoxide and CO2 - Zahra Eshaghi Gorji; Abbas Ali Khodadadi; Siavash Riahi; Timo Repo; Yadollah Mortazavi; Marianna Kemell (Journal of Environmental Sciences, 2023)

Soil frost affects stem diameter growth of Norway spruce with delay - Tapani Repo; Timo Domisch; Jouni Kilpeläinen; Harri Mäkinen (Trees, 2021)
Key message A lack of snow cover and increased soil freezing may not only have short-term impacts on trees but longer-lasting lagged effects on radial growth. Abstract Soil temperature and soil frost intensity are affected by the depth of insulating snow cover and the timing of snowmelt which are predicted to change by climate warming. This may increase tree growth if there is less soil freezing or decrease growth if there is no insulating snow cover, but frost temperatures still exist. Previously, we showed that the changes in soil frost by snow manipulations in a ~ 50-year-old stand of Norway spruce [ Picea abies (L.) Karst.] in eastern Finland in two winters (2005/2006 and 2006/2007) led to short-term changes in physiology, morphology, and the growth of the shoots and roots. The treatments were: (1) control with natural insulating snow accumulation and melting; (2) snow removal during winter; and (3) snow removal in winter and insulation at the top of the forest floor in late winter to delay soil thawing. In this study, we examined the lagged effects of those treatments by radial trunk increment cores during the nine-year recovery period after the termination of the treatments. Annual ring width index (AWI) was calculated for each year by normalization of the ring width in the respective year in proportion to the ring width in the last year (2005) before the treatments. No differences in AWI were found between the treatments before or during the snow manipulation period. However, differences started to appear 1 year after the treatments were finished, became significant 4 years later in 2011 and lasted for 3 years. The radial increment was lower in the treatment with snow removed than in the control and in the treatment with insulation to delay soil thawing, but there were no differences between the latter two treatments. The results indicate that a lack of snow cover may not only have short-term impacts but longer-lasting consequences on the radial growth of trees. The positive effects of prolonged growing season by the increasing summer temperatures on forest growth predicted for the boreal region may therefore not be fully realised due to the negative effects of decreased snow cover and increasing soil freezing.

Direct Compression of Cellulose and Lignin Isolated by a New Catalytic Treatment - Anna Penkina; Osmo Antikainen; Maija Hakola; Sirpa Vuorinen; Timo Repo; Jouko Yliruusi; Peep Veski; Karin Kogermann; Jyrki Heinämäki (AAPS PharmSciTech, 2013)

Sugar End-Capped Poly-d,l-lactides as Excipients in Oral Sustained Release Tablets - Sirpa Vuorinen; Jyrki Heinämäki; Osmo Antikainen; Mohammed Lahcini; Timo Repo; Jouko Yliruusi (AAPS PharmSciTech, 2009)